The Suffering of Indigenous Communities: Environmental Racism in Cherie Dimaline’s The Marrow Thieves - Amanolahi, Anahita (Satura, 2022)
Climate change and racism, both inextricably intertwined, are two of the biggest challenges of this century. Evidence of heightened exposure to environmental hazards in communities of color and their unreasonable exposure to air pollution is mounting, according to an essay by American emergency medicine physician Renée Salas, published in The New England Journal of Medicine. These facts undergird the concept of “environmental racism” – a notion long regarded as a fringe issue that has now clawed its way back into the limelight, thanks to growing awareness of both climate change and racism.